Efficient New Synthesis of N‐Arylbenzo[b]furo[3, 2‐d]pyrimidin‐4‐amines and Their Benzo[b]thieno[3, 2‐d]pyrimidin‐4‐amine Analogues via a Microwave‐Assisted Dimroth Rearrangement. (27th August 2013) - Loidreau, Yvonnick; Dubouilh‐Benard, Carole; Marchand, Pascal; Nourrisson, Marie‐Renée; Duflos, Muriel; Buquet, Catherine; Corbière, Cécile; Besson, Thierry
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>